Swept-source optical coherence tomography angiography in diagnosing radiation retinopathy after choroidal melanoma plaque brachytherapy - Magdalena Kal; Michał Brzdęk; Aleksandra Stypuła-Wypchło; Dorota Zarębska-Michaluk (Studia Medyczne)
Radiation retinopathy is ischaemic damage to the retina and choroid following brachytherapy of intraocular tumours and head and neck tumours. It can lead to vision loss in patients treated with radiation due to choroidal melanoma. Patients following this type of treatment should be systematically monitored for tumour recurrence, metastases, and ischaemic radiation retinopathy. Follow-up should include a fundus examination and additional tests such as optical coherence tomography angiography (OCTA), fluorescein angiography (FA), and B-scan ultrasonography. OCTA proves to be a valuable diagnostic tool for early detection and treatment of radiation retinopathy, offering detailed vascular maps and effectively identifying radiation retinopathy features, complementing traditional methods like fluorescein angiography.